2020
DOI: 10.3390/ani10081255
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Topical Anaesthesia Wound Management Formulation on Pain, Inflammation and Reduction of Secondary Infections after Tail Docking in Lambs

Abstract: We examined several procedures for surgical tail docking; with and without general anaesthesia (GA), including the use of a topical wound gel formulation to provide pain relief (PR) and improve healing after surgery, containing local anaesthetics lignocaine and bupivacaine, with cetrimide and adrenalin. Forty-four lambs were recruited into four equal cohorts: Groups A and C, the tail was excised with a scalpel without anaesthesia or stitches; Groups B and D, the tail was surgically excised and stitched under G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…By day 9, the lesions in the TS-treated cohort had almost entirely disappeared, remaining at 0 cm through day 12 and 15. This is consistent with recent findings that healing of FMD lesions (Windsor et al, 2020) and induced husbandry wounds (Ferrer et al, 2020;Roberts & Windsor, 2019) is enhanced following topical treatment with TS, despite likely depletion of the actives in the formulation. This may be attributable to inclusion of a gel matrix providing prolonged protection for lesion and wound recovery.…”
Section: Discussionsupporting
confidence: 92%
“…By day 9, the lesions in the TS-treated cohort had almost entirely disappeared, remaining at 0 cm through day 12 and 15. This is consistent with recent findings that healing of FMD lesions (Windsor et al, 2020) and induced husbandry wounds (Ferrer et al, 2020;Roberts & Windsor, 2019) is enhanced following topical treatment with TS, despite likely depletion of the actives in the formulation. This may be attributable to inclusion of a gel matrix providing prolonged protection for lesion and wound recovery.…”
Section: Discussionsupporting
confidence: 92%
“…Further, as the product contains an antiseptic, use could also diminish the risks of secondary infections, with TS offering a non-antimicrobial therapeutic option for treating Of interest, was a recent observation that a lower rate of secondary infection occurred following application of TS during surgical tail-docking of lambs, enabling the consideration of replacing routine antibiotic cover with this topical anaesthetic and antiseptic wound formulation. 14 The positive response to therapy observed in two reported studies on the use of this product for clinical FMD, accompanied by an absence of adverse side-effects, suggest this novel approach to viral therapy is worthy of further consideration, particularly if the findings in this preliminary trial of viricidal activity are found to be consistent in future studies. The product invokes positive and prolonged pain-relieving and wound healing effects in livestock following blockage of nociception during treatment of wounds and lesions from aversive husbandry procedures and epitheliotropic virus infections, as described.…”
mentioning
confidence: 91%
“…[10][11][12] Registration of TS in Europe is pending, although it has been shown to be efficacious in the provision of pain relief and more rapid healing of husbandry lesions in sheep in Australia and Spain. 10,13,14 As TS has a pH of 2.7, it has a potential viricidal impact that may reduce transmission risks, with the formulation potentially aiding healing and avoiding the need for other treatments, including antibiotics. 11,12 This paper describes a preliminary investigation of orf therapy with TS, examining the potential antiviral roles and healing properties of the pain-relief formulation in naturally infected lambs with orf, through viral genome real-time PCR quantification and tissue culture in ovine primary cells.…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm was recently challenged in Spain, where a lowered rate of secondary infection occurred following application of this PRP in an ovine surgical tail-docking study, enabling removal of the routine antibiotic cover usually provided during this intervention. 24 A paradigm shift from routine treatment of FMD and other lesions with antimicrobials that risk AMR, to a new approach that improves animal welfare and may motivate farmer interest in disease reporting, assisting transboundary diseaseoutbreak management, is proposed.…”
Section: Discussionmentioning
confidence: 99%